Quality Management of Moral Learning in Islamic Boarding School - Dadang Muliawan; Iim Wasliman; Usep Kosasih; Yufi Mohammad Nasrullah (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
The problem of this research is motivated by the weakening of the morals of students as a negative impact on the development of science and technology. This study aims, in general, to describe and analyze the management of strengthening the moral quality of students and specifically to define and research (1) the Morals of students in Islamic boarding schools and (2) The process of realizing students' morals in Islamic boarding schools. The research procedure used is a qualitative approach with a case study design. Data collection techniques were carried out by (1) Observation, (2) Interview and (3) Documentation. The results showed that (1) the character of the students in the Islamic boarding school had been sufficiently realized, judging from the indicators of the success of the students that they were able to fulfil several components, including the daily morals of the students and the vision of the Islamic boarding school as well as the moral principles of Lickona, (2) the process of realizing the strengthening of the morals of the students in the Islamic boarding school. This can be seen from all management functions that have been carried out systematically, starting from planning, organizing, implementing, and evaluating (3) Solutions to problems in strengthening students' character. The morals of the students have been quite effective, namely the existence of a particular supervisor for students with difficulties.